2017
DOI: 10.3892/mmr.2017.6822
|View full text |Cite
|
Sign up to set email alerts
|

Associations of common IL-4 gene polymorphisms with cancer risk: A meta-analysis

Abstract: Abstract. Cancer incidence is dramatically increasing worldwide, therefore improved prediction and therapeutic methods are needed. Single nucleotide polymorphisms in cytokine genes may contribute to carcinogenesis. Interleukin (IL)-4 gene polymorphisms have been intensively studied with regard to their associations with cancer. However, the results of these previous studies remain inconclusive. The present study, therefore, aimed to conduct a meta-analysis of previously published studies in order to clarify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…This polymorphism is a 70-bp variable number tandem repeat located in an intron of IL4 , which is an interleukin involved in inflammatory pathways. We did not find other studies relating to this polymorphism and GC, but the increased risk of the development of bladder cancer among the carriers of RP1 allele has been previously described[ 14 , 57 ]. Recently, we reported that the frequency of the RP1 allele of rs79071878 is higher in the North of Brazil (0.414) than in the other regions of the country (mean = 0.233), probably due to the elevated frequency of this marker in Amerindian populations[ 56 ].…”
Section: Discussionmentioning
confidence: 54%
“…This polymorphism is a 70-bp variable number tandem repeat located in an intron of IL4 , which is an interleukin involved in inflammatory pathways. We did not find other studies relating to this polymorphism and GC, but the increased risk of the development of bladder cancer among the carriers of RP1 allele has been previously described[ 14 , 57 ]. Recently, we reported that the frequency of the RP1 allele of rs79071878 is higher in the North of Brazil (0.414) than in the other regions of the country (mean = 0.233), probably due to the elevated frequency of this marker in Amerindian populations[ 56 ].…”
Section: Discussionmentioning
confidence: 54%
“…In subgroup analyses, they stratified by ethnicity and they found that there was evidence in the Asian population for an association between this variant and cancer risk. In a meta-analysis performed on 1896 patients and 2526 controls for IL-4 VNTR variant, Jia et al (28) reported that IL-4 VNTR variant was associated with a higher risk of bladder cancer risk. Also, they showed that IL-4-33CT (rs2070874) variant was correlated with leukemia and oral carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that genetic changes and polymorphisms play an important role in the development of sarcomas [ 12 ]. Furthermore, there is emerging data on genetic polymorphisms associated with susceptibility to a wide range of neoplasms [ 13 , 14 ], which can be reasonably explained by genetic changes and polymorphisms.…”
Section: Discussionmentioning
confidence: 99%